THREADS OF TRADITION: EXPLORING THE HISTORICAL AND ECONOMIC SIGNIFICANCE OF ZARI-ZARDOZI CRAFT IN BAREILLY DISTRICT - Mishra, Shubhangi; Singh, Ajit (ShodhKosh: Journal of Visual and Performing Arts, 2025)
This study explores the rich historical and economic significance of the Zari-Zardozi craft in Bareilly, Uttar Pradesh and examines the current challenges faced by this ancient craft. Employing a multidisciplinary approach, it integrates data from both primary and secondaru sources including personal interviews, economic data, historical records, and contemporary studies to trace the journey of this craft from ancient origins to its current role in the local and national economy. The origin of gold embroidery can be traced back to the Vedas but the craft of Zardozi was first found in Persia which was introduced and popularized in India by the Mughals. The city of Bareilly which is in Uttar Pradesh is a major hub for this intricate Embroidery, the craft holds deep historical, cultural and economical importance in for Bareilly that it is populary known as “Zari Nagri” which means the city of Zari. The study takes a deep dive in understanding about types of Zardozi and tools and techniques that are used to create these beautiful designs. The craft is a historical symbol of opulence and currently providing livelihoods for thousands, including a growing number of women. Yet the industry now confronts profound economic and social challenges such as a drastic fall in local turnover, coupled with abysmally low artisan wages that barely cover basic needs, escalating raw material costs (further burdened by an 18% GST), and fierce competition from cheaper, machine-made alternatives, has severely crippled the sector. The study explores that Artisans are exploited by pervasive middlemen, limited access to formal credit, endure hazardous working conditions leading to severe health issues, and perceive a distinct lack of effective government support. These compounding challenges erode the craft's social prestige, actively deterring younger generations and tragically forcing many skilled individuals to abandon their ancestral trade for less dignified, often menial, labor.